PENGARUH SELF-EFFICACY DAN KEMAMPUAN BERPIKIR KREATIF TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 5 MATARAM TAHUN AJARAN 2023/2024 - Aulia Shara Putri; Ketut Sarjana; Junaidi; Baidowi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the effect of self-efficacy and creative thinking ability on the mathematics learning outcomes of eighth-grade students at SMP Negeri 5 Mataram for the academic year 2023/2024, both partially and simultaneously. This research is quantitative with an ex-post facto research method. The population of this study consists of 254 eighth-grade students at SMP Negeri 5 Mataram for the academic year 2023/2024. A sample of 64 students was selected using simple random sampling technique.The instruments tested were valid and included a self-efficacy questionnaire, a creative thinking ability questionnaire, and a mathematics learning outcome test in the form of multiple-choice questions. The results of the descriptive statistical analysis showed that the average self-efficacy score of students was 57.09, categorized as moderate; the average score for creative thinking ability was 46.98, also categorized as moderate; and the average score for mathematics learning outcomes was 59.76, categorized as low.The results of the study showed that: 1) there was a significant effect of self-efficacy on the mathematics learning outcomes of eighth-grade students at SMP Negeri 5 Mataram in the 2023/2024 academic year, with a contribution of 16.4%; 2) there was a significant effect of creative thinking ability on the mathematics learning outcomes of these students, with a contribution of 14.3%; and 3) there was a jointly significant effect of self-efficacy and creative thinking ability on mathematics learning outcomes, with a combined contribution of 23.7%.